Climate Change and Musculoskeletal Health: Implications for Rehabilitation Medicine - Ahmad J. Abdulsalam; Farooq Azam Rathore; Levent Ozcakar (Journal of the Pakistan Medical Association, 2026)
The relationship between climate change and human health has become increasingly clear as global temperatures rises. The cardiovascular and pulmonary consequences of extreme weather events have been well researched and documented in the literature. However, the effects of climate change on MSK health are not well understood. This mini- review explores the complex relationship between MSK health and climate change particularly global warming. It highlights the emerging challenges for rehabilitation medicine due to the climate change and suggests adaptive approaches to clinical practice. The mechanisms linking environmental factors and MSK health are multifactorial and intricate. Temperature extremes can disrupt tissue physiology, while severe weather events may result in trauma and limit access to healthcare services. In addition, exposure to poor air quality has been associated with the exacerbation of inflammatory MSK conditions. Vulnerable populations including elderly adults, outdoor workers, and those with pre-existing MSK disorders face increased risks from climate changes. Climate-resilient rehabilitation services using telemedicine, mobile units, and environmental monitoring can be important considerations. Further research is suggested to establish evidence-based guidelines for climate-adaptive rehabilitation protocols. Keywords: Environmental health, extreme weather, heat stress, rehabilitation protocols, telerehabilitation, inflammatory arthritis